Mycothiol synthesis by an anomerization reaction through endocyclic cleavage - Manabe, Shino; Ito, Yukishige (Beilstein Journal of Organic Chemistry, 2016)
Mycothiol is found in Gram-positive bacteria, where it helps in maintaining a reducing intracellular environment and it plays an important role in protecting the cell from toxic chemicals. The inhibition of the mycothiol biosynthesis is considered as a treatment for tuberculosis. Mycothiol contains an α-aminoglycoside, which is difficult to prepare stereoselectively by a conventional glycosylation reaction. In this study, mycothiol was synthesized by an anomerization reaction from an easily prepared β-aminoglycoside through endocyclic cleavage.
Keywords: anomerization; aminoglycoside; endocyclic cleavage reaction; inositol; mycothiol